Changes in 18th-Century Japanese Academic Circles and Tongsinsa 通信使 Exchange: Focusing on the Emergence of the Sorai School 徂徠學派 and the Publication Process of the Pildamchanghwajip 筆談唱和集 - Lee, Hyo-Won (International Journal of Korean Humanities and Social Sciences, 2025)
Of the 18th century in Japan, new academic trend that called Soraigaku (徂徠學) have emerged. Soraigaku has expanded the force while criticizing the Neo-Confucianism and poet of Song dynasty (宋詩). In the mid 18th century, Soraigaku is as prevalent widely in Japan. However, in fact, crucial opportunity to Soraigaku has become epidemic, it was for the publication to criticize the Tongsinsa. The Sorai school (徂徠學派) was in conflict relation with Rinke (林家), Mokumon (木門), Jinsaimon (仁齋門). So the opportunity to contact with the Tongsinsa was little. In addition, Sorai school’s literary works aren’t included in Geyrimchnghwajip (鷄林昌和集). So the Sorai school published Munsagisang (問槎畸賞) that include their own literary works. He was severely criticized the Tongsinsa in Munsagisang. As a result, Sorai school’s reputation has become to be known throughout the country. Sorai is to criticize the authority of Tonsinsa which was very high in Japan, so it was able to improve their own phase of school.